Predictive and Prognostic Potentials of Lymphocyte-C-Reactive Protein Ratio Upon Hospitalization in Adult Patients with Acute Pancreatitis - Xu XY; Gao Y; Yue CS; Tang YJ; Zhang ZJ; Xie FJ; Zhang H; Zhu YC; Zhang Y; Lai QQ; Wang XT; Xu JX; et al. (Dove Medical Press, 2024)
Xiao-Yu Xu,1,* Yang Gao,2,* Chuang-Shi Yue,3,* Yu-Jia Tang,4,* Zhao-Jin Zhang,5 Feng-Jie Xie,6 Hong Zhang,6 Yu-Cheng Zhu,7 Yan Zhang,7 Qi-Qi Lai,4 Xin-Tong Wang,4 Jia-Xi Xu,4 Jia-Ning Zhang,4 Bo-Wen Liu,4 Jian-Nan Zhang,4 Kai Kang4 1Department of Critical Care Medicine, The Second People's Hospital of Beihai, Beihai, People's Republic of China; 2Department of Critical Care Medicine, The Sixth Affiliated Hospital of Harbin Medical University, Harbin, People's Republic of China; 3Department of Critical Care Medicine, Henan Provincial People's Hospital, Zhengzhou, People's Republic of China; 4Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, People's Republic of China; 5Department of Critical Care Medicine, The Yichun Central Hospital, Yichun, People's Republic of China; 6Department of Critical Care Medicine, The Hongqi Hospital Affiliated to Mudanjiang Medical University, Mudanjiang, People's Republic of China; 7Department of Critical Care Medicine, The Hongxinglong Hospital of Beidahuang Group, Shuangyashan, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian-Nan Zhang; Kai Kang, Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, 23 Youzheng Street, Nangang District, Harbin, Heilongjiang, 150001, People's Republic of China, Tel +86-13836119816 ; +86-13904618016, Email zhangjiannan@hrbmu.edu.cn; janekk79@126.comPurpose: In this study, our objective was to investigate the potential utility of lymphocyte-C-reactive protein ratio (LCR) as a predictor of disease progression and a screening tool for intensive care unit (ICU) admission in adult patients with acute pancreatitis (AP).Methods: We included a total of 217 adult patients with AP who were admitted to the First Affiliated Hospital of Harbin Medical University between July 2019 and June 2022. These patients were categorized into three groups: mild AP (MAP), moderately severe AP (MSAP), and severe AP (SAP), based on the presence and duration of organ dysfunction. Various demographic and clinical data were collected and compared among different disease severity groups.Results: Height, diabetes, lymphocyte count (LYMPH), lymphocyte percentage (LYM%), platelet count (PLT), D-Dimer, albumin (ALB), blood urea nitrogen (BUN), serum creatinine (SCr), glucose (GLU), calcium ion (Ca2+), C-reactive protein (CRP), procalcitonin (PCT), hospitalization duration, ICU admission, need for BP, LCR, sequential organ failure assessment (SOFA) score, bedside index for severity in AP (BISAP) score, and modified Marshall score showed significant differences across different disease severity groups upon hospitalization. Notably, there were significant differences in LCR between the MAP group and the MSAP and SAP combined group, and the MAP and MSAP combined group and the SAP group, and adult AP patients with ICU admission and those without ICU admission upon hospitalization.Conclusion: In summary, LCR upon hospitalization can be utilized as a simple and reliable predictor of disease progression and a screening tool for ICU admission in adult patients with AP.Keywords: lymphocyte-C-reactive protein ratio, acute pancreatitis, lymphocyte count, C-reaction protein, disease progression, ICU admission, screening tool